The role of the southern african development community on Zimbabwe’s quest for food security - Chiwara, Dadirayi Cathrine (Midlands State University, 2015)
The study sought to establish the role that the Southern African Development Community has played in Zimbabwe’s quest for food security. Food insecurity is a major development problem in Zimbabwe despite food being the most basic of human needs. The study used qualitative research methods to interrogate the research topic. The report looked at the SADC objectives on food security and how these have been translated into programmes that improve the food security situation of Zimbabwe and SADC in general. The results showed that SADC has not played an important role at programme level on Zimbabwe’s quest for food security however the study also revealed that SADC has played a role as a resource centre, providing technical assistance in the form of policy formulation, guidelines and strategies. The body also acts as a conduit for financial assistance into the region by partners who are not willing to have individual country agreements but would want to provide wholesale financing with SADC monitoring and reporting on progress. The researcher reached the conclusion that given the reluctance to cede authority to SADC by member states it is up to member states, including Zimbabwe, to tap into the expertise available at the SADC secretariat to enable them to meet their food security goals.